Adolescent Character Education from Buya Hamka’s Perspective: Tolerance Values in Islamic Education - Fika Hoirina; Kustiana Arisanti; Umi Lailia Maghfiroh (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study examines the values of tolerance in the thought of Buya Hamka and their relevance to adolescent character education within the context of Islamic Religious Education. The study is motivated by the increasing phenomenon of intolerance, bullying, and moral degradation among Indonesian youth, which reflects a gap between the ideal objectives of Islamic Religious Education and contemporary social realities. This research employs a qualitative approach using library research methods. The primary sources consist of Hamka’s major works, namely Falsafah Hidup, Lembaga Hidup, Modern Sufism, and Tafsir Al-Azhar. Data were analyzed using content analysis with a philosophical and pedagogical perspective. The findings reveal that Hamka’s thought contains comprehensive values of tolerance, including tasamuh (forbearance), rahmah (universal compassion), justice (‘adl), and wasathiyyah (moderation), all of which are rooted in Qur’anic theological principles. These values are highly relevant for integration into Islamic Religious Education to foster tolerant, inclusive, moderate, and morally grounded adolescents. This study offers a conceptual framework for tolerance education based on Indonesian Islamic thought that is contextual and applicable to contemporary multicultural society.